Chemometric Optimization of Trypsin Digestion Method Applying Infrared, Microwave and Ultrasound Energies for Determination of Caseins and Ovalbumin in Wines - Salazar-Gonzalez, R (Springer, 2021)
Caseins and ovalbumin are frequently used as wine fining agents to remove undesirable compounds like polymeric phenols. Their presence in wines is a subject of concern because may cause adverse effects on susceptible consumers, especially when their presence is not labeled. A key step for its determination is trypsin digestion, which is considered the bottleneck of bottom-up approach workflow because usually requires several hours. To reduce this time, the objective of this work was to carry out a chemometric optimization of trypsin digestion method applying infrared, microwave and ultrasound energies to determine caseins and ovalbumin in wines. The conditions of each accelerated digestion method were optimized using a Response Surface Methodology based on central composite design. The parameters optimized were digestion time and trypsin: protein ratio. The response variable evaluated was digestion yield, which was determined through the peak area of each protein transition determined by liquid chromatography-mass spectrometry. The most effective technique was microwave followed by ultrasound and infrared. Since optimal values of microwave and ultrasound-assisted digestion were the same, the later was chosen considering sample preparation and cost. Applying the proposed approach, a reduction of ca. 140 and 240-fold on digestion time was achieved compared with optimized and non-optimized conventional methods, respectively. With this workflow, both proteins were digested in a single 3 min process allowing its detection by liquid chromatography-mass spectrometry at µg L−1 level, which is ca. 60 times lower than the current limit of 0.25 mg L−1. © 2020, Association of Food Scientists & Technologists (India).